Effects of Adding Cherry Laurel (Laurocerasus Officinalis) on Some Physicochemical and Functional Properties and Sensorial Quality of Tarhana - Tarakçi, Z.; Anil, M.; Koca, I.; İslam, A. (Wageningen Academic Publishers, 2013)
Tarhana, a traditional fermented food produced from a mixture of wheat flour and yoghurt, is widely consumed in Turkey. The aim of this study was to investigate the effect of cherry laurel pulp on the physico-chemical, functional and sensorial characteristics of tarhana. Tarhana samples with 0, 5, 10, 15 and 20% cherry laurel pulp were manufactured. The statistical analysis showed that addition of pulp affected titratable acidity, pH, total phenolic, antioxidant capacity, foaming capacity, foam stability, viscosity, colour and sensorial scores significantly. Pulp addition decreased dry matter, titratable acidity, water absorption capacity, foaming capacity, foam stability and L* (lightness), a* (redness) and bz.ast; (yellowness) colour values significantly (P<0.05). There were significant differences (P<0.05) in viscosity values between the control tarhana and the samples made with cherry pulp. However, increasing pulp increased significantly (P<0.05) pH, total phenolic, ferric reducing antioxidant power, radical scavenging activity. The most acceptable sensory scores were obtained with 5.0 and 10.0% added pulp. In the production of flavoured tarhana sample, samples with these cherry laurel pulp levels are recommended. © 2013 Wageningen Academic Publishers.
Keywords: Antioxidant; Cherry Laurel Fruit; Colour; Sensorial Properties; Tarhana; Viscosity